"The Southeast Asian Approach" to Counter-Terrorism:: Learning from Indonesia and Malaysia - Ramakrishna, Kumar (Journal of Conflict Studies, 2005)
ABSTRACT US counter-terror doctrine appears to assume that undermining Islamist terror networks such as al-Qaeda and its Southeast Asian affiliate Jemaah Islamiyah requires increasing state capacities and promoting intelligence cooperation to eliminate terror cells and their logistics lines within Southeast Asia, while promoting good governance to ensure that terror networks do not transform failed state environments into sanctuaries. This article argues that while such a real-time, short-term counter-terrorist strategy is certainly important, it needs to be complemented by a longer-term approach designed to neuter the ability of terror networks to regenerate. This is why a counter-terrorism strategy designed to eradicate as far as possible the ideological and political sources of Muslim discontent is just as vital. Rejecting "top-down," one-size-fits-all approaches formulated in Washington, the article articulates a "bottom-up" Southeast Asian indirect strategy to combat Islamist terror within the region. It shows how certain aspects of the Malaysian and Indonesian experiences respectively may offer clues as to how such a Southeast Asian indirect strategy, encompassing a mix of counterterrorism and counter-terrorist elements in which the former play a central role, may be formulated.